Metal line emission from galaxy haloes at z ≈ 1. Issue 1 (4th April 2023) - Dutta, Rajeshwari; Fossati, Matteo; Fumagalli, Michele; Revalski, Mitchell; Lofthouse, Emma K; Nelson, Dylan; Papini, Giulia; Rafelski, Marc; Cantalupo, Sebastiano; Arrigoni Battaia, Fabrizio; Dayal, Pratika; Longobardi, Alessia; et al.
ABSTRACT: We present a study of the metal-enriched halo gas, traced using Mg ii and [O ii ] emission lines, in two large, blind galaxy surveys – the MUSE (Multi Unit Spectroscopic Explorer) Analysis of Gas around Galaxies (MAGG) and the MUSE Ultra Deep Field (MUDF). By stacking a sample of ≈600 galaxies (stellar masses M_* ≈ 10 6–12 M_ ), we characterize for the first time the average metal line emission from a general population of galaxy haloes at 0.7 ≤ z ≤ 1.5. The Mg ii and [O ii ] line emission extends farther out than the stellar continuum emission, on average out to ≈25 and ≈45 kpc, respectively, at a surface brightness (SB) level of 10 −20 erg s^-1 cm^-2 arcsec^-2 . The radial profile of the Mg ii SB is shallower than that of the [O ii ], suggesting that the resonant Mg ii emission is affected by dust and radiative transfer effects. The [O ii ] to Mg ii SB ratio is ≈3 over ≈20–40 kpc, also indicating a significant in situ origin of the extended metal emission. The average SB profiles are intrinsically brighter by a factor of ≈2–3 and more radially extended by a factor of ≈1.3 at 1.0 < z ≤ 1.5 than at 0.7 ≤ z ≤ 1.0. The average extent of the metal emission also increases independently with increasing stellar mass and in overdense group environments. When considering individual detections, we find extended [O ii ] emission up to ≈50 kpc around ≈30–40 per cent of the group galaxies, and extended (≈30–40 kpc) Mg ii emission around two z ≈ 1 quasars in groups, which could arise from outflows or environmental processes.